Primerjava triboloških lastnosti mineralnih in repičnih mazalnih olj - Vižintin, Jože (Strojniški vestnik, 2001)
In the study, the test equipment and the methods for determination of the mechanical physical and chemical properties of rapeseed-based oils are introduced. The same equipment and methods were already used for testing the selected mineral-based oil. The mechanical properties were performed on a high-frequency test device for friction and wear measurement (SRV) and FZG test rig. The oil selection procedure and the properties of tested oils are also described. The results are selected rapeseed oils with the same viscosity at a starting working temperature as a corresponding mineral-based oil of a higher-ISO grade.
Keywords: olja repična; SRV; FZG; maziva; repično olje; mehanske lastnosti; preizkušanje; mazanje